Engaging leaders: The challenge of inspiring collective commitment in universities - Gentle, P.; Forman, Dawn (Routledge, 2014)
Addressing the question of how leadership can work most successfully in universities, Engaging Leaders strengthens the sense of shared professional knowledge and capability amongst leaders in higher education. Presenting a narrative of change which not only spells out why universities need to work differently, this book also takes the reader through clear practical steps which any practising leader can take in order to build a collaborative professional culture which supports and challenges all members of an academic community. Using a selection of case studies from UK and international universities, the book explores why working collectively remains a fundamental challenge for many higher education institutions and looks at the benefits of creating a collective commitment throughout universities. It covers: • action learning and professional learning communities • emotionally-intelligent organisational cultures • feedback as an intrinsic tool • building partnerships and collaborations • Higher Education and public value • cultures of innovation and sustainable practices. Engaging Leaders is for those who see themselves as leaders in higher education, whether or not this is recognised in their job title. It provides stimulating perspectives on what they might do to become more engaged and engaging, and includes examples of inspiring practice which is already making a difference in universities, colleges and new private providers. It will be of value to established managers as well as those new in post, and also for those participating in postgraduate programmes.